High tumor mutation burden indicates better prognosis in colorectal cancer patients with KRAS mutations - Wang, Jianlei; Song, Jianping; Liu, Zeyang; Zhang, Tingxiao; Liu, Yanfeng (Frontiers in Oncology, 2022)
Objective: Colorectal cancer (CRC) is a common type of malignant tumor of the digestive tract. Tumor mutation burden (TMB) is a potential prognostic indicator of numerous malignant tumors. This study investigated the prognostic value of TMB in CRC. Methods: Clinical and somatic mutation data of CRC patients from the MSKCC and TCGA cohorts were included in the analyses. The genetic landscape was visualized using the maftools package in R software. Survival curves were constructed using the Kaplan–Meier method, and Cox regression analysis was used to confirm that TMB is an independent prognostic indicator. A nomogram was used to construct the prognostic model, and the C-index, calibration curve, and decision curve analyses were used to evaluate the prognostic model. Results: APC mutations indicated longer overall survival (OS), whereas KRAS mutations indicated shorter OS in CRC patients. For all included patients, there was no significant difference in the OS between the TMB-high and TMB-low groups. For patients with KRAS mutations, the OS in the TMB-high group was longer than that in the TMB-low group. Cox regression analysis showed that TMB was an independent prognostic factor in CRC patients with KRAS mutations. Hence, the nomogram prognostic model using TMB had good accuracy and clinical applications. Conclusions: High TMB indicates a better prognosis in CRC patients with KRAS mutations, thus confirming that TMB is valuable in clinical applications.